Social responsibility of business in the focus of economic security of enterprises - Loktionova , Ya. (Ways to Improve Construction Efficiency, 2022)
The article considers a comprehensive approach to integrating business social responsibility into the system of ensuring the economic security of enterprises in the conditions of a transformational economy, global instability and the latest challenges of a social and environmental nature. It is proven that social responsibility ceases to be an optional tool of corporate image and instead acquires the status of an integral factor in the formation of enterprise stability, adaptability to crisis phenomena, increasing competitiveness and long-term development.The implementation of socially responsible practices contributes to the minimization of reputational, personnel, legal and environmental risks, strengthening trust from stakeholders, reducing conflicts in the work environment, improving interaction with government bodies, partners and communities. The social orientation of business at the same time acts as a lever for increasing its investment attractiveness, ensuring access to cheaper financial resources and international development programs.The article presents the author's vision of social responsibility as a system-forming element of the concept of economic security of an enterprise. A structure of socially responsible practices adapted to the realities of the Ukrainian business environment under martial law is proposed, which includes: employee support, local community development, environmental responsibility, ethical business behavior, transparency and accountability. It is revealed that it is the social orientation of business that allows you to effectively counteract social, institutional and reputational threats.It is concluded that the development of corporate social responsibility is a strategic direction for increasing the economic security of the enterprise, which allows you to form a sustainable business model capable of reproducing capital in conditions of uncertainty and systemic threats. It is emphasized that in modern conditions, social responsibility should be integrated into the risk management strategy, corporate culture and tools for assessing the effectiveness of management decisions.